Acacetin Ameliorates Experimental Colitis in Mice via Inhibiting Macrophage Inflammatory Response and Regulating the Composition of Gut Microbiota - Ren, Junyu; Yue, Bei; Wang, Hao; Zhang, Beibei; Luo, Xiaoping; Yu, Zhilun; Zhang, Jing; Ren, Yijing; Mani, Sridhar; Wang, Zhengtao; Dou, Wei (Frontiers in Physiology, 2021)
Acacetin, a natural dietary flavonoid abundantly found in acacia honey and citrus fruits, reportedly exerts several biological effects, such as anti-tumor, anti-inflammatory, and anti-oxidative effects. However, the effects of acacetin on intestinal inflammation remain unclear. We sought to investigate whether acacetin ameliorates inflammatory bowel disease (IBD) in mice with dextran sulfate sodium (DSS)-induced ulcerative colitis (UC). Our results suggest that acacetin alleviates the clinical symptoms of DSS-induced colitis, as determined by body weight loss, diarrhea, colon shortening, inflammatory infiltration, and histological injury. Further studies showed that acacetin remarkably inhibited both the macrophage inflammatory response in vitro and levels of inflammatory mediators in mice with colitis. In addition, some features of the gut microbiota were disordered in mice with DSS-induced colitis, as evidenced by a significant reduction in microbiota diversity and a marked shift in bacterial profiles. However, acacetin treatment improved this imbalance and restored gut microbiota to levels that were similar to those in normal mice. In conclusion, our work presents evidence that acacetin attenuates DSS-induced colitis in mice, at least in part, by inhibiting inflammation and regulating the intestinal microbiota.